The Effectiveness of Billboards of Billboards as Political Campaign Media for Elected DPRD Members for the 2024-2029 Period in Kendari City - Larisu, Zulfiah; Dilla, Sumadi; Harjuddin, Laode; Rajab, Muhammad (STMIK Widya Cipta Dharma, 2024)
This study aims to analyze the effectiveness of billboards as a political campaign medium for elected DPRD members for the 2024–2029 period in Kendari City. The research employs a qualitative method, with data collected through interviews, observations, and document analysis. The informants in this study were elected DPRD members in the 2024 election from all electoral districts (DAPIL) of Kendari City, selected purposively. Observations focused on billboards installed in each electoral district, while document analysis utilized secondary data obtained from the KPU, BAWASLU, and Kendari City DPRD institutions. The data was analyzed using an interactive model that includes data collection, reduction, analysis, and presentation. The results indicate that most elected DPRD members in Kendari City employed billboards as a key political campaign tool. These billboards were self-designed, incorporating effective billboard elements and were utilized by both incumbent and new members. Typically, the billboards featured photos, candidate serial numbers, names and titles, party logos, and short campaign messages. Some billboards also included photos of party leaders as well as presidential and vice-presidential candidates supported by their respective parties. The sizes of the billboards ranged from 2 meters x 3 meters to 4 meters x 6 meters, with placements concentrated around electoral districts and along main roads. The strategic design and placement of billboards are expected to enhance public appeal and engagement.